Circularly Polarized Triangular Patch Antenna - Toktas, Abdurrahim (Recent Advances in Electrical & Electronic Engineering, 2022)
Background: Circularly polarized (CP) antenna is an effective choice for wireless systems due to its insensitivity to the orientations of electromagnetic waves. Objective: A novel CP triangular patch antenna (CPTA) system is designed for ultra-wideband (UWB) applications. Methods: The CPTA, with a total size of 40.6 x 40.9 x 1.6 mm3, comprises a triangular patch positioned on the aperture of a V-shaped ground plane and a feeding network that powers the two corners of the patch. The network consists of a T-shaped divider with a 50 Ohm microstrip transmission line (MTL) and two 100 Ohm MTLs, and two matching strips are inserted at the end of the MTLs. Results: The antenna system shows UWB performance for both impedance bandwidth (IM-BW) of 4-11 GHz and axial ratio bandwidth (AR-BW) of 3.5-8.0 GHz. A detailed review is further carried out to manifest the superiority of CPTA over the state-of-the-art technology. Conclusion: It thus provides compatible IM-BW and AR-BW for UWB operations due to its optimal compact design.
Keywords: electromagnetic waves